Potenzialità e sfide dell’intelligenza artificiale (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
The article, based on the writings collected in the issue, proposes a constitutionally oriented perspective of artificial intelligence (AI). Dealing with the main potentials and threats of AI, it suggests some constitutional principles as the basis for an effective regulation of the phenomenon, calling for a precise and direct human responsibility.
Keywords: Artificial intelligence; constitutional law; bid data; responsibility; automated decisions